Deconstruction of biomass into lignin oil and platform chemicals over heteropoly acids with carbon-supported palladium as a hybrid catalyst under mild conditions. (December 2021) - Zhang, Haichuan; Zhang, Hui; Tian, Shenglong; Fu, Shiyu
Highlights: SiW12 exhibits excellent activity towards the lignin linkages and glycosidic bonds. The conversion of biomass was significantly enhanced by introducing into Pd/C. Lignocellulose was completely disassembled into monophenols and platform compounds. Monophenols yield of 34.91% for bagasse and 43.55% for eucalyptus were observed. Abstract: In this work, near-complete conversion of lignocellulosic biomass and high products yields were achieved through catalytic transfer hydrogenolysis (CTH) in isopropanol using a heteropoly acid SiW12 synergistic with Pd/C catalyst at a relatively mild condition. The performances of various heteropoly acids and catalytic conditions were extensively examined. The results confirmed that SiW12 exhibited the highest activity on disrupting C–C linkages and C-O linkages than H2 WO4, PW12, and PMo12 . 34.91 wt% and 43.55 wt% monophenols were achieved for hydrogenolysis of bagasse and eucalyptus, respectively, at their optimal temperature for 5 h. Characterization studies on the lignin oil revealed that the notable structural changes were observed including the breaking of the side chain alkyl-aryl ether bonds and glycosidic bonds, while methoxyl groups were retained. Additionally, particle size of feedstock also has significant impact on the distribution and yields of the monophenols.